Spontaneous atraumatic rupture of the urinary bladder following alcohol intoxication: A rare case report - Shritik Devkota; Sugat Adhikari; Manbir Singh; Samiksha Lamichhane; Dipendra Adhikari; Bishal Koirala; Harsha Bhola (Clinical Case Reports)
Key Clinical Message Consideration of spontaneous urinary bladder rupture in the differential diagnosis of acute abdominal pain for alcohol‐abusing patients is crucial for ensuring timely surgical intervention and preventing life‐threatening complications due to its high associated morbidity and mortality. Abstract Spontaneous rupture of the urinary bladder (SRUB) is a rare but critical urological emergency, typically associated with malignancy, neurogenic dysfunction, or previous radiation therapy. Here, we present a unique case of SRUB in a 65‐year‐old chronic alcoholic male who presented with acute lower abdominal pain following heavy alcohol consumption. Initial evaluations revealed leukocytosis, elevated serum creatinine levels, and ultrasound findings suggestive of bladder rupture. Computed tomography confirmed the diagnosis, indicating an intraperitoneal rupture with associated hematoma. Immediate surgical repair was performed, leading to a successful outcome. This case underscores the importance of considering SRUB in patients with acute abdominal pain, especially in the context of alcohol intoxication, and highlights the diagnostic and therapeutic challenges associated with this condition. Early recognition and intervention are crucial to prevent life‐threatening complications associated with urinary bladder rupture.